Exploring the Civic Architecture of Accountability in Contemporary Public Policy Systems - Sulaksono, Sulaksono; Hardyansah, Rommy; Marzuki, Al-Araf Assadallah; Marsal, Antonino Pedro (Journal of Social Science Studies, 2024)
This study investigates the mechanisms through which civil society organizations (CSOs) monitor and influence the implementation and accountability of public policy. Drawing from interdisciplinary literature spanning governance, political science, and development studies, the analysis reveals that CSOs engage in multifaceted strategies including grassroots data collection, policy analysis, strategic litigation, digital monitoring, and transnational advocacy. These functions allow CSOs to operate as both watchdogs and co-governors in contemporary public administration. The findings highlight that the efficacy of these monitoring practices depends on legal environments, institutional openness, resource access, and civic agency. CSOs enhance transparency by transforming technical policy information into public knowledge and creating participatory spaces where citizens can hold institutions accountable. The review also emphasizes the growing importance of digital innovation and transnational networks in expanding the scope of civil society monitoring. Challenges such as civic space contraction, co-optation, and fragmentation are acknowledged, but CSOs’ adaptive resilience continues to sustain their influence. The study concludes that civil society oversight reconfigures democratic governance by embedding accountability within everyday civic practices. It argues for policy frameworks that facilitate institutional responsiveness to CSO engagement and calls for empirical research that further examines relational dynamics, knowledge translation, and collaborative monitoring paradigms.